The rs11684747 and rs55790676 SNPs of ADAM17 influence tuberculosis susceptibility and plasma levels of TNF, TNFR1, and TNFR2 - Choreño-Parra, José Alberto; Ramon-Luing, Lucero A.; Castillejos, Manuel; Ortega-Martínez, Emmanuel; Tapia-García, Alan Rodrigo; Matías-Martínez, Melvin Barish; Cruz-Lagunas, Alfredo; Ramírez-Martínez, Gustavo; Gómez-García, Itzel Alejandra; Ramírez-Noyola, Jazmín Ariadna; Garcia-Padrón, Beatriz; López-Salinas, Karen Gabriel; et al. (Frontiers in Microbiology, 2024)
Introduction The proteolytic activity of A Disintegrin and Metalloproteinase 17 (ADAM17) regulates the release of tumor necrosis factor (TNF) and TNF receptors (TNFRs) from cell surfaces. These molecules play important roles in tuberculosis (TB) shaping innate immune reactions and granuloma formation. Methods Here, we investigated whether single nucleotide polymorphisms (SNPs) of ADAM17 influence TNF and TNFRs levels in 224 patients with active TB (ATB) and 118 healthy close contacts. Also, we looked for significant associations between SNPs of ADAM17 and ATB status. TNF, TNFR1, and TNFR2 levels were measured in plasma samples by ELISA. Four SNPs of ADAM17 (rs12692386, rs1524668, rs11684747, and rs55790676) were analyzed in DNA isolated from peripheral blood leucocytes. The association between ATB status, genotype, and cytokines was analyzed by multiple regression models. Results Our results showed a higher frequency of rs11684747 and rs55790676 in close contacts than ATB patients. Coincidentally, heterozygous to these SNPs of ADAM17 showed higher plasma levels of TNF compared to homozygous to their respective ancestral alleles. Strikingly, the levels of TNF and TNFRs distinguished participant groups, with ATB patients displaying lower TNF and higher TNFR1/TNFR2 levels compared to their close contacts. Conclusion These findings suggest a role for SNPs of ADAM17 in genetic susceptibility to ATB.